2002
DOI: 10.1161/01.res.0000038151.57577.19
|View full text |Cite
|
Sign up to set email alerts
|

Statin-Induced Expression of Decay-Accelerating Factor Protects Vascular Endothelium Against Complement-Mediated Injury

Abstract: Abstract-Complement-mediated vascular injury is important in the pathophysiology of atherosclerosis and myocardial infarction. Because recent evidence shows that statins have beneficial effects on endothelial cell (EC) function independent of lipid lowering, we explored the hypothesis that statins modulate vascular EC resistance to complement through the upregulation of complement-inhibitory proteins. Human umbilical vein and aortic ECs were treated with atorvastatin or simvastatin, and decay-accelerating fact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
56
0
1

Year Published

2003
2003
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(62 citation statements)
references
References 52 publications
5
56
0
1
Order By: Relevance
“…Incubation with cycloheximide alone led to a superinduction of steady-state DAF mRNA, consistent with previous reports. 12 Addition of both CRP and cycloheximide led to a rise in steady-state DAF mRNA similar to that observed with cycloheximide alone, which was significantly lower than DAF mRNA levels after only CRP treatment ( Figure 2B). Similar results were obtained when examining cell-surface DAF expression ( Figure 2C).…”
Section: Crp-induced Daf Expression Requires Increased Mrna and De Nosupporting
confidence: 67%
See 2 more Smart Citations
“…Incubation with cycloheximide alone led to a superinduction of steady-state DAF mRNA, consistent with previous reports. 12 Addition of both CRP and cycloheximide led to a rise in steady-state DAF mRNA similar to that observed with cycloheximide alone, which was significantly lower than DAF mRNA levels after only CRP treatment ( Figure 2B). Similar results were obtained when examining cell-surface DAF expression ( Figure 2C).…”
Section: Crp-induced Daf Expression Requires Increased Mrna and De Nosupporting
confidence: 67%
“…18 Our data suggest that CRP-induced expression of DAF depends on the synthesis of an intermediate transcriptional activator and that the observed increase in DAF expression is functionally relevant, as indicated by the reduction in complement-mediated cell lysis. However, unlike vascular endothelial growth factor, tumor necrosis factor-␣, interferon-␥, or statins, 12,17,18 CRP was also able to induce the expression of the additional complement inhibitors CD46 and CD59, suggesting that the changes mediated by CRP arise through a combination of signaling pathways. Although not tested, the ability of CRP to activate mitogen-activated protein kinases and the transcription factors nuclear factor-B and activator protein-1, 19 linked to increased complement inhibitor expression, 12,17,18 may be responsible for the increase in DAF, CD46, and CD59 observed after CRP stimulation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, statins increase endothelial nitric oxide synthase expression, 14 decrease smooth muscle cell proliferation, 15 reduce matrix metalloproteinase activity and tissue factor production by macrophages, 16,17 increase fibrinolytic activity, 18 and have immunomodulatory and antiinflammatory actions such as increasing resistance to complement 19 and decreasing dendritic cell maturation. 20 Many of these effects are reversed only with geranylgeranyl pyrophosphate and not with farnesyl pyrophosphate, suggesting that inhibition of Rho isoprenylation by statins is the predominant mechanism by which statins exert their antiatherogenic activities.…”
Section: Discussionmentioning
confidence: 99%
“…Having demonstrated that augmenting KLF2 levels within the Treg compartment is sufficient to promote peripheral tolerance, we next tested if this event could be replicated by simvastatin. Of note, statins have an immunosuppressive effect on endothelial cells, including decreased MHC class II expression, decreased expression of P-selectin and CD40, increased surface expression of complement inhibitory molecules, and increased production of nitric oxide (31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41). Because the endothelial compartment contributes to symptoms of aGVHD (42)(43)(44)(45), these pleiotropic effects precluded the systemic use of simvastatin to test Treg-mediated tolerance.…”
Section: Increased Klf2 Expression Within the Treg Compartment Augmentsmentioning
confidence: 99%